Efficacy of Hypertonic Saline-Epinephrine Local Injection Around the Anal Side before Endoscopic Papillectomy for Ampullary Tumors - Naoki Okano; Yoshinori Igarashi; Ken Ito; Saori Mizutani; Hiroki Nakagawa; Kouji Watanabe; Yuuto Yamada; Kensuke Yoshimoto; Yuusuke Kimura; Susumu Iwasaki; Kensuke Takuma; Seiichi Hara; et al. (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims Bleeding is a complication of endoscopic snare papillectomy for ampullary tumors. This study aimed to investigate the clinical efficacy of hypertonic saline-epinephrine (HSE) local injection before endoscopic papillectomy for prevention of bleeding. Methods We retrospectively reviewed the data of 107 consecutive patients with ampullary tumors who underwent endoscopic papillectomy. The rates of en bloc resection, pathological resection margins, and prevention of immediate or delayed bleeding in the simple snaring resection group (Group A) and the HSE injection group (Group B) were compared. Results A total of 44 and 63 patients were enrolled in Groups A and B, respectively. The total complete resection rate was 89.7% (96/107); the clinical complete resection rates in Group A and Group B were 86.3% (38/44) and 92.1% (58/63), respectively (p=0.354). Post-papillectomy bleeding occurred in 22 patients. In Groups A and B, the immediate bleeding rates were 20.5% (9/44) and 4.8% (3/63), respectively (p=0.0255), while the delayed bleeding rates were 7% (3/44) and 11% (7/63), respectively (p=0.52). The rates of positive horizontal and vertical pathological margin in both groups were 27% and 16%, respectively. Conclusions HSE local injection was effective in preventing immediate bleeding and was useful for safely performing endoscopic papillectomy for ampullary tumors.